2018
DOI: 10.1080/00913847.2018.1477403
|View full text |Cite
|
Sign up to set email alerts
|

2706 km cycling in 2 weeks: effects on cardiac function in 6 elderly male athletes

Abstract: The results suggest that repeated moderate intensity exercise in elderly men was associated with a transient increase in cardiac biomarkers while cardiac function remained unaltered. A favorable reduction in blood lipids and diastolic blood pressure were seen for >28 h after the end of activity. An unexplained symptomless severe plasma hyponatremia developed in 3 of 6 subjects 28 h after the end of activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The study participants experienced a decrease in cardiorespiratory fitness, a decrease in maximal fat oxidation rate (MFO) and a decrease in insulin sensitivity (HOMA‐IR) after the exercise intervention, suggesting that the intervention negatively impacted these markers of physiological and metabolic health. 19 , 20 We speculated that these apparently detrimental adaptations to extreme endurance exercise could have been age‐specific and some support for this contention is provided by Easthope and collegues who demonstrated somewhat larger muscle damage in 46 ± 6 years versus 31 ± 7 years old master and younger athletes, respectively after a 55 km trail running competition. 21 To test this possibility, we conducted the present study, which examines the physiologic and metabolic impact of repeated prolonged moderate intensity exercise (7–10 h/day for 15 consecutive days at ≈63% HR max ) in two cohorts of seven men, age 30 ± 5 years or age 65 ± 6 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study participants experienced a decrease in cardiorespiratory fitness, a decrease in maximal fat oxidation rate (MFO) and a decrease in insulin sensitivity (HOMA‐IR) after the exercise intervention, suggesting that the intervention negatively impacted these markers of physiological and metabolic health. 19 , 20 We speculated that these apparently detrimental adaptations to extreme endurance exercise could have been age‐specific and some support for this contention is provided by Easthope and collegues who demonstrated somewhat larger muscle damage in 46 ± 6 years versus 31 ± 7 years old master and younger athletes, respectively after a 55 km trail running competition. 21 To test this possibility, we conducted the present study, which examines the physiologic and metabolic impact of repeated prolonged moderate intensity exercise (7–10 h/day for 15 consecutive days at ≈63% HR max ) in two cohorts of seven men, age 30 ± 5 years or age 65 ± 6 years.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, we investigated the metabolic and physiologic impact of 14 days of consecutive cycling over a total distance of approximately 2700 km in a cohort of six older men (61 years). The study participants experienced a decrease in cardiorespiratory fitness, a decrease in maximal fat oxidation rate (MFO) and a decrease in insulin sensitivity (HOMA‐IR) after the exercise intervention, suggesting that the intervention negatively impacted these markers of physiological and metabolic health 19,20 . We speculated that these apparently detrimental adaptations to extreme endurance exercise could have been age‐specific and some support for this contention is provided by Easthope and collegues who demonstrated somewhat larger muscle damage in 46 ± 6 years versus 31 ± 7 years old master and younger athletes, respectively after a 55 km trail running competition 21 .…”
Section: Introductionmentioning
confidence: 99%
“…At a first glance, these results tend to disagree with most publications on this topic. Indeed, previous data reported a transient decrease of ventricular systolic function after prolonged multistage exercise [ 7 , 10 , 16 18 ]. The systolic dysfunction severity seemed to be positively related to the characteristics of the endurance exercise carried out such as its intensity and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it makes sense to think that the physiological stress placed on the myocardium during repeated and prolonged efforts may result in a cumulative decrement in cardiac function, subsequently delaying the recovery process. Surprisingly, this cumulative cardiac fatigue was not found in most of studies that investigated the impact of multi-day prolonged exercise on cardiac function [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Troponin elevation may result from several mechanisms: parietal mechanical stress in response to pressure or volume overload ( 18 ), tachycardia ( 19 ), massive release of catecholamines ( 20 ), direct action of PAMPs (pathogen-associated molecular patterns) or lipopolysaccharides in sepsis ( 21 ), or viral, bacterial, or immune myocarditis ( 22 ). Previous studies have found a significant increase in cardiac biomarkers [N-terminal pro-brain natriuretic peptide (NT-proBNP) and troponin] during long-distance exercises ( 23 , 24 ), with unclear significance ( 25 , 26 ). Recently, it has been observed that a troponin exercise-induced increase above the 99th percentile could be an early marker of mortality and cardiovascular events ( 27 ) notably in participants with hypertension ( 28 ).…”
Section: Introductionmentioning
confidence: 99%